ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN UMKM PADA MASA PANDEMI COVID-19 TAHUN 2021 - Muhammad Rapii; Agus Riswanto; Lia Febriani (Gorontalo State University, 2023)
At the global economic level, the Covid-19 pandemic has provided a very significant impact on the country's domestic economy and the existence of Small and Medium Micro Business (SMEs). The Organisation for Economic Co-operation and Development (OECD) stated that the pandemic has implications for the threat of a major crisis marked by the cessation of production activities in many countries, the reduction of public consumption, loss of cosumer confidence, and stock crash which ultimately leads to uncertainty. This study aims to determine: (1) the effect of social distancing of income, (2) the effect of raw material prices of income, (3) the effect of technology of income, (4) the effect of consumption of income. This study was a causal research. The subjects were SMEs in the village of Sikur Induk as many as 50 SMEs. The sampling method was used Non Probability sampling technique. The technique of collecting data was used questionaires. Validity and reliability tests conducted on 50 people. Data analysis technique was used multiple linear regression. The results of this study indicated that(1) there is a negative the effect of social distancing of income. Proved by a regression the value of t is greather than t table (-2,198 -2,014), (2) There is a positive effect of raw material prices of income. Proved by a regression the value of t is greather than t table (2,136 2,014), (3) there is a positive effect of technology of income. Proved by a regression the value of t is greather than t table (3,708 2,014), (4) there is a negative effect of consumption of income. Proved by a regression the value of t is greather than t table (-2,863 -2,014), (5) there is a positive influence of social distancing, raw material prices, technology, and consumption of income. Proved by a regression the value of F is greather than F table (9,367 2,58).